2022
DOI: 10.1021/acsanm.2c02314
|View full text |Cite
|
Sign up to set email alerts
|

Probing a Proximity-Coupling-Induced Hybrid Anomalous Hall Effect in Epitaxial MnBi2Te4/Bi2Te3 Nanostructures

Abstract: The alliance of magnetism and non-trivial topology provides a promising platform for exploring exotic topological quantum states such as high temperature quantum anomalous Hall insulator and robust axion insulator, and the strategies of dilute magnetically doped, intrinsic magnetic materials and proximity of magnetic materials have been successfully pursued to achieve magnetic ordering in topological insulators. However, the intricate interplay between the topological insulator and intrinsic magnetic topologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Recently, the molecular beam epitaxy (MBE) technique was successfully utilized to grow MBT-based thin films to investigate their intriguing topological quantum phenomena. ,, Two growth recipes were applied for fabricating MBT-based thin films, including the alternating deposition of Bi 2 Te 3 and MnTe layers followed by in situ annealing, and the coevaporation of Mn, Bi, and Te elements combined with the delicate adjustment of the Mn/Bi flux ratio. ,, Angle-resolved photoemission spectroscopy (ARPES) measurements revealed linearly dispersed TSS, and magnetic and magneto-transport characterizations depicted anomalous hysteresis loops in MBT-based thin films, ,, verifying their inherent MTI features. Chang et al reported that their MBT films contain a Mn-doped Bi 2 Te 3 impurity by examining the nonsquare anomalous Hall (AH) hysteresis loops.…”
mentioning
confidence: 99%
“…Recently, the molecular beam epitaxy (MBE) technique was successfully utilized to grow MBT-based thin films to investigate their intriguing topological quantum phenomena. ,, Two growth recipes were applied for fabricating MBT-based thin films, including the alternating deposition of Bi 2 Te 3 and MnTe layers followed by in situ annealing, and the coevaporation of Mn, Bi, and Te elements combined with the delicate adjustment of the Mn/Bi flux ratio. ,, Angle-resolved photoemission spectroscopy (ARPES) measurements revealed linearly dispersed TSS, and magnetic and magneto-transport characterizations depicted anomalous hysteresis loops in MBT-based thin films, ,, verifying their inherent MTI features. Chang et al reported that their MBT films contain a Mn-doped Bi 2 Te 3 impurity by examining the nonsquare anomalous Hall (AH) hysteresis loops.…”
mentioning
confidence: 99%